The Ambivalent Perspective on Shamanism in the Joseon Era of Korea - Staci Kim (International Journal of Religious and Cultural Studies, 2022)
The Joseon Dynasty (1392–1910) was founded based on Confucian ideology, which strongly emphasized rationalism and formality. As it influenced the entirety of the Joseon society, shamanism that had been branded as an ‘obscene and superstitious practice’ by the Confucian ruling class was oppressed institutionally on various dimensions from the life and manners of people to rituals throughout the Joseon era. However, it was able to survive, gaining the advocacy from ordinary people as well as the support of royal families. Although the predominant view on the Joseon era posed an anti-syncretic religious landscape based on a powerful Confucian identity, various religions co-existed under the multi-religious circumstances. This ambivalence still exists in today’s Korean society in term of shamanism.